The level of Understanding of FIK Unimed Basketball UKM Students About Fiba Regulations in 2022 - Riza, Ade Ros; Marpaung, Denni Rahman; Azandi, Filli; Ibrahim; Raswin (Journal Coaching Education Sports, 2025)
The purpose of this study was to measure the level of understanding of FIK UNIMED basketball UKM students of FIBA regulations in 2022. This research is descriptive with a quantitative approach, using a survey method and one variable, namely the level of understanding of the FIBA 2022 regulations, which is translated into three indicators: game rules, violations, and fouls. The research subjects were students who participated in extracurricular basketball, with the sampling technique using total sampling, resulting in 14 students as samples. Data were collected using research instruments in the form of multiple choice questions that had been validated by experts (expert judgment). Data analysis was carried out with descriptive statistics presented in percentage form. The results showed that the level of understanding of FIK UNIMED basketball UKM students about FIBA regulations in 2022 had an average of 24.21 which was included in the "Moderate" category. Details of the categorization results are as follows: "Very Low" category of 0%, "Low" category of 29% or 4 students, "Medium" category of 43% or 6 students, "High" category of 14% or 2 students, and "Very High" category of 14% or 2 students.